Neuromarketing in Market Research: Eye Tracking Application - Dijana Ćosić (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
The goal of this paper is to explore the benefits of neuromarketing, in general, and the eye tracking method, in particular, in market research, and to consider their ethical implications. In an example of a typical case study I will try to show how eye tracking can be deployed to analyse the unconscious visual perception of a TV commercial by the participants in the study. I analysed a TV commercial for readymade soups, in which five different readymade soups where advertised. The sample contains 21 participants. With the help of eye tracking method in “Gazepoint” software we have discovered that one scene drew attention much more than the others. In addition to this, I review the literature on benefits of eye tracking as a complement to more traditional methods. I also present an overview of ethical issues related with this method.
Keywords: M3; 330; neuromarketing; eye tracking; market research; ethics